Linehan's Dialectical Behaviour Therapy (DBT) for borderline personality disorder: Overview and adaptation - Swales, M; Heard, H; Williams, J (2000)
Dialectical Behaviour Therapy (DBT) is a structured, time-limited, cognitive behavioural treatment originally developed for Borderline Personality Disorder clients who have chronic parasuicidal problems. The therapy integrates individual psychotherapy with concurrent skills training, access to skills generalisation and team consultation for therapists. Initial outcome studies by Linehan and colleagues conducted in the US suggest that the therapy successfully lowers attrition rate, parasuicidal episodes and psychiatric in-patient days. The effect on parasuicidal behaviour and psychiatric in-patient days appear to outlast the therapy by at least a year. This paper overviews the therapy and examines how it may be used in day-to-day clinical practice in other cultural settings. We suggest that any adaptation or modification to DBT should be done in the context of a theoretical model of which psychological processes underlie the treatment effects and with due attention to the advantages and disadvantages of working within the NHS structure.